Modelling the economics of agroforestry at field- and farm-scale - Garcia de Jalon, S. (2017)
This report (Deliverable 6.18) assesses the economics of agroforestry systems at field- and farm-scales and compares them with alternative land uses such as arable cropping, pasture and forestry. This analysis is undertaken in terms of financial profitability (e.g. from a farmer perspective) and economic benefits (e.g. from a societal perspective)